Head-To-Head Comparison of Arrhythmia Discrimination Performance of Subcutaneous and Transvenous ICD Arrhythmia Detection Algorithms: The START Study - GOLD, MICHAEL R.; THEUNS, DOMINIC A.; KNIGHT, BRADLEY P.; STURDIVANT, J. LACY; SANGHERA, RICK; ELLENBOGEN, KENNETH A.; WOOD, MARK A.; BURKE, MARTIN C. (Journal of cardiovascular electrophysiology, 2012)
Arrhythmia Detection with S‐ICD Versus Transvenous ICDs. Background: The development of a totally subcutaneous implantable defibrillator (S‐ICD) system requires a new approach for arrhythmia detection. To evaluate arrhythmia discrimination of one such system, the Subcutaneous versus Transvenous Arrhythmia Recognition Testing (START) study was designed as a prospective, multicenter trial comparing simulated sensing performances of the S‐ICD system with single‐ (SC‐TV) and dual‐chamber transvenous (DC‐TV) implantable cardioverter‐defibrillator (ICD) systems. Methods: At ICD implantation, induced ventricular and atrial arrhythmias were recorded simultaneously in transvenous (right ventricular [RV]→superior vena cava [SVC]+ Coil) and cutaneous electrode configurations. Recorded signals of ventricular (n = 46) and atrial arrhythmias (n = 50) with ventricular rates >170 bpm from 64 patients were used to compare detection performance of the S‐ICD system with TV‐ICD systems from 3 manufacturers. Appropriate detection of ventricular tachyarrhythmias was assessed with devices programmed in single‐zone (rate ≥170 bpm) and dual‐zone configurations (ventricular fibrillation ≥240 bpm; ventricular tachycardia ≥170 bpm). S‐ICD specificity performance for supraventricular arrhythmias was compared to single‐ and dual‐chamber devices in a dual‐zone configuration. Results: Appropriate detection of ventricular tachyarrhythmias for subcutaneous and TV devices in single‐ and dual‐zone configurations was 100% and >99%, respectively. Specificity for supraventricular arrhythmias was significantly better for the S‐ICD system compared to 2 of 3 TV systems, as well as the composite of TV devices (98.0%[S‐ICD] vs 76.7%[SC‐TV range: 64.0–92.0%] vs 68.0%[DC‐TV range: 32.7–89.8%; P < 0.001]). Conclusion: Appropriate ventricular arrhythmia detection is excellent for all ICD systems evaluated; however, specificity of supraventricular arrhythmia discrimination by the S‐ICD system is better than discrimination by 2 of 3 TV systems.